2019
DOI: 10.1002/jmrs.358
|View full text |Cite
|
Sign up to set email alerts
|

Coronary CT radiation dose reduction strategies at an Australian Tertiary Care Center – improvements in radiation exposure through an evidence‐based approach

Abstract: Introduction Coronary CT Angiography (CCTA) is a rapidly increasing technique for coronary imaging; however, it exposes patients to ionising radiation. We examined the impact of dose reduction techniques using ECG‐triggering, kVp/mAs reduction and high‐pitch modes on radiation exposure in a large Australian tertiary CCTA service. Methods Data on acquisition modes and dose exposure were prospectively collected on all CCTA scans from November 2009 to March 2014 at an Australian tertiary care centre. A dose reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
(47 reference statements)
1
5
0
Order By: Relevance
“…In this study, the CTDI vol for BMI < 25 and ≥25 kg/m 2 were 20.03 and 24.83 mGy, respectively, which are consistent with previous reports [ 25 , 26 ]. Over the past decades, various dose reduction strategies have been proposed for CCTA scans [ 27 , 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the CTDI vol for BMI < 25 and ≥25 kg/m 2 were 20.03 and 24.83 mGy, respectively, which are consistent with previous reports [ 25 , 26 ]. Over the past decades, various dose reduction strategies have been proposed for CCTA scans [ 27 , 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…Recent research using ECG-based tube current modulation and dualsource CT coronary angiography revealed radiation dose values ranging from 7 to 9 mSv 13 . In this study, when it represented the effective dose graphically for the two hospitals, it found that the effective doses for males (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) mSv were lower than females (13-29) mSv; this result was presented in Figure-3 for both the hospitals (X) and (Y). This difference in effective doses for males and females may be due to differences in tissue composition and weight.…”
Section: Discussionmentioning
confidence: 72%
“…Several radiation dose reduction techniques have been introduced in recent years in CTCA including prospective ECG-triggered scanning, heart rate control, reduced tube voltage and tube current modulation. 5 This has resulted in rapid improvements in the reduction of radiation dose from CTCA; the British Society of Cardiovascular Imaging and the British Society of Cardiac Computed Tomography conducted an audit of radiation dose from coronary CT angiography in 2014 and 2016. In the 2-year interval, they identified a 30% reduction in the median exam DLP for prospective ECG-gated acquisitions with tube current padding.…”
Section: Discussionmentioning
confidence: 99%
“… 4 There are several ways to reduce effective dose from CTCA investigations including prospective ECG triggered scanning, heart rate control, tube current modulation, optimised contrast monitoring, iterative reconstruction, and high pitch scanning. 5,6 …”
Section: Introductionmentioning
confidence: 99%